Logistics Departure Scheduling Information System Using the Fifo (First In, First Out) Method at CV. RAS - Rissa Azzahra Damanik; Ali Ikhwan (Jurnal E-Komtek, 2026)
RAS is a trucking transportation company that provides goods delivery services to various destinations. Currently, logistics scheduling is performed manually, leading to scheduling conflicts, recording errors, and delivery delays that reduce operational efficiency. This study aims to design and develop a web-based logistics scheduling information system implementing the First in First Out (FIFO) method to improve logistics management. The research adopted the Research and Development approach using the Waterfall software development model, consisting of requirements analysis, system design, implementation, testing, and maintenance. The FIFO method schedules deliveries according to the sequence of incoming shipment requests, ensuring fair and systematic processing. The developed web-based system simplifies scheduling, data management, and monitoring of logistics activities. System evaluation confirmed that all functional features operated as expected. The results demonstrate that the proposed system effectively minimizes scheduling conflicts, improves data accuracy, enhances operational efficiency, and supports better decision-making for logistics scheduling at CV. RAS.